Practical approaches to method validation and essential instrument performance verification - Chan, Chung Chow.; Lam, Herman; Zhang, Xue-Ming. (Hoboken, N.J. : Wiley, 2010)
"The objective of this book is provide information in same practical, hands-on manner as the first book "Analytical Method Validation and Instrument Performance Verification", on important, but more advance topics. It will focus on additional and supplemental methods, instruments, and electronic systems that are used in pharmaceutical, biopharmaceutical, and clinical testings. These tests will generate reliable data that is in compliance with current Good Manufacturing Practices (cGMP) and will follow Good Analytical Practices"--Provided by publisher.
(Publisher-supplied data ) Overview of Risk Based Approach to Phase Appropriate Validation and Instrument Qualification / Phase Appropriate Method Validation / Analytical Method Verification, Method Revalidation, and Method Transfer / Validation of PAT Applications / The Validation of Near Infrared Systems for Raw Material Identification / Cleaning Validation / Risk Based Validation of laboratory Information Management Systems (LIMS) / Performance Qualification and Verification of Balance / Performance Verification of NIR Spectrophotometers / Operational Qualification in Practice for Gas Chromatography Instruments / Performance Verification on RI, Fluorescence, Evaporative Light Scattering Detection / Instrument Qualification and Performance Verification for Particle Size Instruments / Method Validation, Qualification, and Performance Verification for Total Organic Carbon (TOC) Analyzers / Instrument Performance Verification ? Micro Pipettes / Instrument Qualification and Performance Verification for Automated Liquid Handling Systems / Performance Qualification and Verification in Powder X-ray Diffraction.
Complement to: Method validation and instrument performance verification / edited by Chung Chow Chan ... [et al.]. c2004.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2021. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Drugs -- Analysis -- Methodology -- Evaluation; Laboratories -- Equipment and supplies -- Evaluation; Laboratories -- Instruments -- Evaluation; Electronic books